The Appropriateness of Monthly Expense Management of KIP-K Recipient Students with Christian Values - Debora Gultom; Norlyn V Pakpahan; Ritayana P Silalahi; Sucy Novika Tarigan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The purpose of this study was to assess the feasibility of managing the expenses of KIP-K recipients, aligning them with Christian values such as honesty, responsibility, thrift, and social concern. The method used was a quantitative descriptive approach, using a survey technique using a questionnaire distributed to eight students. The results showed that the majority of respondents had used KIP-K funds for primary educational needs (50% strongly agreed) and prioritized needs over wants (50% strongly agreed). Furthermore, respondents were also noted to exhibit a high level of responsibility and honesty in using these funds. However, several weaknesses were identified in terms of budget planning, spending control, and savings habits and maintaining an emergency fund.